Gender Inequality And Renewable Energy: How Women’s Interests and Lack of Participation Leading to Women Marginalization in Renewable Energy in Indonesia - Antasya, Alya; Kersana, Rekha (Journal of Indonesian Social Sciences and Humanities, 2023)
The discussion on gender within the realm of renewable energy has not been extensively explored. This article aims to elucidate the forms of gender inequality that occur in the renewable energy sector and the factors contributing to the low participation of women, despite their high interest and concern for environmental and energy issues. This article employs the Feminist Climate Justice framework to examine this issue, including case studies of women’s participation in the renewable energy sector in two rural areas of Indonesia, namely South Papua and Nusa Tenggara. The findings of this article assert that the gender inequality occurring within the energy sector, specifically the marginalization of women, is not due to a lack of interest or competence in the energy field. Instead, several other factors are at play, such as cultural norms and customs, societal stigma/stereotypes towards women, the double burden, an unsupportive environment, and renewable energy policies that have not comprehensively addressed the concept of just transition and active women’s participation.